2014
DOI: 10.1080/1528008x.2014.889532
|View full text |Cite
|
Sign up to set email alerts
|

Selling Strategies and Shopping Behavior—An Example of Taiwanese Guided Package Tourists to Mainland China Destinations

Abstract: China has become the most visited destination in the world for international tourists. The number of Taiwanese tourists going to China on guided tours has increased; "shopping" and "optional tours" are the two most controversial consumption experiences for them due to price competition. This study aims to investigate the Taiwanese guided package tourists' shopping intentions and behavior when traveling in China and also to examine how their shopping behaviors are influenced by sales representatives, local tour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2015
2015
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 44 publications
0
6
0
1
Order By: Relevance
“…Consumer behaviour is never entirely reducible to the structures that exercise subtle control. However, studying these structures – in this case, sales strategies – offers a reversed perspective with respect to consumption (Chang, ); promoting the sale of duty‐free products involves the exercise of a corporate‐friendly, ‘top down’ creativity that choreographs the realms within which consumers exercise their personal creativity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consumer behaviour is never entirely reducible to the structures that exercise subtle control. However, studying these structures – in this case, sales strategies – offers a reversed perspective with respect to consumption (Chang, ); promoting the sale of duty‐free products involves the exercise of a corporate‐friendly, ‘top down’ creativity that choreographs the realms within which consumers exercise their personal creativity.…”
Section: Resultsmentioning
confidence: 99%
“…This paper is situated at the interface between selling and mobility; a world-in-motion, when carefully understood by business interests, offers opportunities to make money. The study of consumer behaviour within the context of tourism-orienting shopping (Park, Reisinger, & Noh, 2010;Doong, Wang, & Law, 2012;Jensen, 2012) could benefit from the development of related research that examines well-documented sales strategies designed to stimulate demand (Chang, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Psychological abuse, which is designed to intimidate another person, appears to be used occasionally to maintain a steady position. Inevitably, emotional blackmail (Susan and Donna, 1998) was often used by tour bus drivers to promote their own interests within the appraisal and coping process which generated stress outcomes or discomfort symptoms to tour guides or tour participants (see Chang, 2014). The tour guides, who serve as a mediator between bus drivers and customers, often find themselves working in a tense atmosphere with the tour bus drivers.…”
Section: Discussionmentioning
confidence: 99%
“…Tour bus drivers in certain countries are perceived as low-paid and commission sensitive; they tend to work long hours due to the intensive travel itineraries of package tours (see Chang, 2014). A report from Commonwealth Magazine, a leading Taiwanese magazine, indicated that the average age of tour bus drivers is near 49 and the industry is facing aging problems.…”
Section: Tour Bus Drivers In Taiwanmentioning
confidence: 99%
“…Gerek ulusal çalışmalarda (Güzel, 2007;Müküs, 2009;Nebioğlu, 2013;Şahin, 2012;Tetik, 2012;Yarcan, 2007) gerekse uluslararası çalışmalarda (Black ve Ham, 2015;Chan, 2015;Chang, 2014;Chang, 2006;Grabowski ve Genge, 2000;Jonasson ve Scherle, 2012;Kuo vd. 2015;Lin vd.…”
Section: Sonuç Ve Tartişmaunclassified